PENGARUH PIJAT OKSITOSIN TERHADAP PENINGKATAN PENGELUARAN KOLOSTRUM PADA IBU POST PARTUM DI PMB WIDARSIH SRAGEN - Nurita, Siti; Triani , Yuyun (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: The importance of colostrum in newborn babies can optimize the formation of the body's immune system so that it tends to be better protected from various diseases such as flu, diarrhea and pneumonia. WHO revealed that giving colostrum to babies can help prevent 22% of infant deaths due to the formation of better immunity and prevention of infections that can occur in babies. Problems in giving colostrum such as producing little or no colostrum. Oxytocin massage is one way to overcome irregularities in colostrum production. Objective: To determine the effect of oxytocin massage on increasing colostrum production in post partum mothers. Research Method: Pre-Experiment with pretest posttest one group design, consecutive sampling technique, sample of 20 respondents, observation sheet instrument and oxytocin massage SOP and paired sample t-test. Results: The results of the paired sample t-test p value 0.000 <0.05. Conclusion: There is an effect of oxytocin massage on increasing colostrum production in post partum mothers.